What Is the True Impact of Cognitive Impairment for People Living with Multiple Sclerosis? A Commentary of Symposium Discussions at the 2020 European Charcot Foundation - Sarah A. Morrow; Paola Kruger; Dawn Langdon; Nektaria Alexandri (Neurology and Therapy, 2023)
Abstract Multiple sclerosis (MS) is a chronic, neurodegenerative, inflammatory condition usually associated with physical disability. Clinical care has been skewed toward the physical manifestations of the disease, yet a range of silent symptoms occurs including the cognitive aspects of MS. In a 2018 meeting of MS in the 21st Century (MS21), an international steering committee comprising both specialists and patient experts recognised that the ‘invisible symptoms’ of MS pose a significant challenge to patient engagement. These findings prompted the European Charcot Foundation (ECF) MS21 symposium (2020), where a panel consisting of two leading MS clinicians and an MS patient expert (who were all members of the MS21 steering group) gathered to discuss the impact of cognitive impairment on the everyday lives of people with MS. The perspectives and experiences of the panellists are summarised in this paper. The key points raised were that (1) the cognitive manifestations of MS are under-recognised and have consequently been undermanaged from a clinical perspective and (2) cognitive impairment due to MS has a significant impact upon daily living and patient quality of life. During discussions about how these challenges can be addressed, the panel advocated for an improvement in education about cognitive symptoms for people living with MS and healthcare professionals (HCPs) to raise awareness about this aspect of MS. Furthermore, the panel emphasised the importance of open and proactive communication between HCPs and their patients with MS about cognitive symptoms to reduce the stigma attached to these symptoms. In the opinion of the panel, future clinical trials which include cognitive outcomes as key endpoints are needed. Reflecting this point, cognitive impairment in MS care also needs to be treated as an important disease symptom, as is done with physical symptoms of the disease. Implementing early and routine cognition screening and promoting measures for protecting cognition to people living with MS, such as cognitive rehabilitation and a ‘brain-healthy’ lifestyle, are actions which can drive forward the recognition of cognitive impairment as a care priority. If prioritised as highly as physical disability in both the MS care and clinical drug development setting, and proactively discussed in conversations between HCPs and patients with MS, the ‘invisibility’ of cognitive impairment in MS can be lifted and a better quality of life can be promoted for people living with MS.